DEPDC1B promotes development of cholangiocarcinoma through enhancing the stability of CDK1 and regulating malignant phenotypes - Zhang, Zhenhai; Wang, Xinxing; Nie, Peihua; Qin, Yejun; Shi, Junping; Xu, Shifeng (Frontiers in Oncology, 2022)
Cholangiocarcinoma (CCA) is the second most common primary tumor of the hepatobiliary system. At present, the therapeutic efficiency of cholangiocarcinoma is fairly low and the prognosis is poor. The root cause is that the molecular mechanism of the occurrence and development of CCA is largely unclear. This work intended to clarify the role of DEPDC1B in the progress of CCA through cellular biology research strategies, and further clarify the molecular mechanism of CCA. Clinical tissue related detection showed that the expression level of DEPDC1B in tumor tissues was significantly higher than that in normal tissues, and it was positively correlated with tumor grade. Knockdown of the endogenous DEPDC1B of CCA cells can significantly inhibit cell proliferation and migration, while promoting cell apoptosis and blocking the cell cycle. DEPDC1B overexpression induced the opposite effects. Studies in animal models also showed that the down-regulation of DEPDC1B can reduce the tumorigenicity of CCA cells. In addition, through gene profiling analysis and molecular biology studies, we found that CDK1 may be an important downstream mediator of DEPDC1B, protein stability of which was significantly decreased through ubiquitin-proteasome system in DEPDC1B knockdown cells. Moreover, knockdown of CDK1 can weaken the promotion of CCA caused by DEPDC1B overexpression. In summary, our research showed that DEPDC1B plays an important role in the development of CCA, and its targeted inhibition may become one of the important methods to inhibit the progress of CCA.